2016
DOI: 10.1111/radm.12205
|View full text |Cite
|
Sign up to set email alerts
|

Business model innovation and decision making: uncovering mechanisms for coping with uncertainty

Abstract: As a research subject, business model innovation spans the strategy, innovation, and entrepreneurship fields. Yet, despite the importance of the concept, prior work has paid little attention to how decision-makers cope with uncertainty and gain understanding about interdependencies in new business model configurations. To address this gap, we combine top-down theorising and evidence-based exploration and seek to unpack some of the coping mechanisms that operate in the evolutionary view of business model innova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 56 publications
2
60
0
1
Order By: Relevance
“…Our selection of BM elements is analogous to the conceptualization by Spieth and Schneider (2016), which has been empirically derived in multiple workshops with managers, practitioners, and innovation experts using an inductive approach. Recent research has also shown that the understanding of business models converges to these components (Saebi, Lien, & Foss, 2017;Schneckenberg, Velamuri, Comberg, & Spieth, 2017). Consequently, our definition can build on both theoretical and practical foundations.…”
Section: Casadesusmentioning
confidence: 98%
See 4 more Smart Citations
“…Our selection of BM elements is analogous to the conceptualization by Spieth and Schneider (2016), which has been empirically derived in multiple workshops with managers, practitioners, and innovation experts using an inductive approach. Recent research has also shown that the understanding of business models converges to these components (Saebi, Lien, & Foss, 2017;Schneckenberg, Velamuri, Comberg, & Spieth, 2017). Consequently, our definition can build on both theoretical and practical foundations.…”
Section: Casadesusmentioning
confidence: 98%
“…It extends the activity-based concept with regard to the revenue model and effectively balances value proposition and value delivery, which fits our intent to capture BM consistency in a well-adjusted and comprehensive manner. Recent research has also shown that the understanding of business models converges to these components (Saebi, Lien, & Foss, 2017;Schneckenberg, Velamuri, Comberg, & Spieth, 2017). Our selection of BM elements is analogous to the conceptualization by Spieth and Schneider (2016), which has been empirically derived in multiple workshops with managers, practitioners, and innovation experts using an inductive approach.…”
Section: Business Models and Business Model Innovationmentioning
confidence: 99%
See 3 more Smart Citations